Small town research in Germany - Status quo and recommendations - Lars Porsche; Annett Steinführer; Stephan Beetz; Peter Dehne; Stefan Fina; Katrin Großmann; Tim Leibert; Anita Maaß; Heike Mayer; Antonia Milbert; Robert Nadler; Martin Sondermann (Verlag der ARL - Akademie für Raumforschung und Landesplanung, 2019)
Urban studies in Germany are traditionally oriented towards large cities. The structures, meanings and functions of small towns are not sufficiently perceived and differentiated in scientific or political debates. Adequate research on small towns requires systematic, comparative, inter- and transdisciplinary approaches. Traditional attributions should be questioned critically and small towns should be examined empirically in their diversity and differentiation. This involves paying attention to external influences and heterogeneous internal structures as well as to regional functions and interdependencies. The availability and generation of statistical data, which also make small-scale analyses possible, are just as necessary as more comprehensive studies, which go beyond limited case studies. Finally, also research funding and academic teaching should address small towns more systematically than it has been the case in the past. This position paper presents recommendations for research, university teaching, official statistics and research funding in the field of small town research. The Ad-hoc Working Group focused on small town research in Germany and German- language literature, respectively.
urn:nbn:de:0156-01149
Keywords: 710; Small towns; Small town research; Urban development; Development of rural areas; Urbanstudies; Spatial research; Germany